Frequency of spontaneous BOLD signal shifts during infancy and correlates with cognitive performance. (April 2015) - Alcauter, Sarael; Lin, Weili; Smith, J. Keith; Goldman, Barbara D.; Reznick, J. Steven; Gilmore, John H.; Gao, Wei
Highlights: Peak-frequency of spontaneous BOLD signal increases during infancy. Increments of power at the peak-frequency showed spatially dependent patterns. Power at the peak-frequency in 1-year olds correlates with cognitive performance. ABSTRACT: Numerous studies have been conducted to delineate the early development of different functional networks, based on measuring the temporal synchronization of spontaneous blood oxygenation level-dependent (BOLD) signals acquired using resting state functional MRI (rsfMRI). However, little attention has been paid to the change of the frequency properties of these signals during early brain development. Such frequency properties may reflect important physiological changes and potentially have significant cognitive consequences. In this study, leveraging a large ( N = 86 subjects), longitudinal sample of human infants scanned during the first two years of life, we aimed to specifically delineate the developmental changes of the frequency characteristics of spontaneous BOLD signals. Both whole-brain and network-level examinations were carried out and the frequency–behavior relationship was explored. Our results revealed a clear right-ward shift of BOLD signal frequency during the first year of life. Moreover, the power at the peak-frequency for sensorimotor and lateral visual networks correlates with domain-specific Mullen Scales in 1-year-olds, suggesting the behavioral significance of the BOLD signal frequency during infancy. Findings from this study shed light into early functional brain development and provide a new perspective for future searches for functional developmental abnormalities.